Identification and Structural Characterization of the Precursor Conformation of the Prion Protein which Directly Initiates Misfolding and Oligomerization. Issue 6 (24th March 2017) - Moulick, Roumita; Udgaonkar, Jayant B.
Abstract: To identify and structurally characterize the precursor conformation of the prion protein (PrP), from which misfolding and aggregation directly commence, has been a long-standing goal. Misfolding converts the α-helical, non-pathogenic functional form of PrP to pathogenic, β-structured oligomeric and amyloidogenic forms, which are the cause of prion diseases. Susceptibility to sporadic prion disease correlates well with the propensity of PrP to misfold to cytotoxic, proteinase K resistant oligomeric conformations at low pH. In this study, mutagenesis at the hydrophobic core of the mouse PrP has been shown to stabilize a monomeric unfolding intermediate (I), which is populated significantly at equilibrium at low pH. Importantly, the rate of formation of β-structured oligomers at low pH is found to correlate well with the extent to which this intermediate is populated. The misfolding process is limited by the dimerization of I, indicating that I is the monomeric precursor conformation that directly initiates misfolding. Structural and thermodynamic characterization by native-state hydrogen–deuterium exchange mass spectrometry studies indicate that the precursor conformation is a partially unfolded form of PrP that forms under misfolding-prone solvent conditions. Graphical Abstract: Stochastic fluctuations of the native state of the prion protein populate at least two partially unfolded forms, PUF1 and PUF2, in misfolding-promoting solvent conditions. Of these two high energy intermediates, PUF2, wherein the α1-β2 subdomain separates and unfolds from the hydrophobic core comprising of helices α2 & α3, acts as the direct monomeric precursor to misfolding and formation of β-rich, protease resistant, cytotoxic prion oligomers. Highlights: Dearth of structural information on conformations initiating prion misfolding Mutagenesis stabilizes a monomeric intermediate (I) in mouse PrP. Misfolding and oligomerization process are limited by the dimerization of I. Native-state hydrogen exchange studies indicate that I is partially unfolded. Structural loss in N required to initiate misfolding directly is identified.